The effects of shoulder injury on kinaesthesia: A systematic review and meta-analysis. Issue 1 (February 2015) - Fyhr, Charlotte; Gustavsson, Linnéa; Wassinger, Craig; Sole, Gisela
Abstract The aim of this systematic review was to synthesize the evidence for changes for proprioceptive variables consisting of movement and position sense in participants with glenohumeral musculoskeletal disorders. Five databases were searched until 13th August 2013. Methodological quality was assessed and meta-analyses were performed for active and passive joint reposition sense (AJPS and PJPS) and movement sense, determined with threshold to detection of passive motion (TTDPM). The search yielded 17 studies, four of which were classified as having high methodological quality, seven as moderate and six as low quality. For participants with post-traumatic glenohumeral instability, pooled findings indicate moderate evidence for higher TTDPM for involved shoulders compared to control groups and the contralateral uninvolved side, indicating decreased movement sense. For AJPS and PJPS there was moderate to limited evidence for significant increased errors for involved compared to uninvovled shoulders, but not when compared to the control groups. Limited evidence was found for decreased AJPS acuity for patients with chronic rotator cuff pain and for patients with unspecified shoulder pain compared to healthy controls. Movement sense is most likely to be impaired after shoulder injury involving post-traumatic instability when compared to the contralateral shoulder and to controls, while deficits for AJPS and PJPS are more likely to be evident compared to the contralateral shoulder in participants with glenohumeral musculoskeletal disorders.